AI Based Assistance To Reduce Suicidal Tendency Among Youngsters - Rawat, Bhupesh; Bist, Ankur Singh; Mulyati; Fakhrezzy, Muhammad; Octavyra, Regina Dinda (Pandawan, 2023)
Suicidal tendency among youngsters is one of emerging issue in society.This not only results in loss of life but also has disruptive psychosocial and adverse socio-economic effects. It accounts for 1.4% of all deaths. It is also reported that men die more than women. If we look at male to female ratio regarding suicide death, then it is 1.5 to 1 and is highest in richest countries. Each year, approximately 800,000 people die by suicide worldwide. Fast life style, academic pressure, relationships, drug addiction etc, are major causes of this. This is exacerbated by the presence of new factors that arise as a result of the COVID-19 outbreak, which puts new pressures on society, which of course worsens the mental condition of today's society.Governments and NGOs are highly concerned about it. In this paper, we are concerned about the role of technology to prevent it. We will discuss how artificial intelligence can help in keeping the wellbeing of the mental state of human beings. Our focus would be on use of artificial intelligence in predicting and preventing suicide attempt. We will share our perspective on how other techniques excluding AI can help to alleviate this menace.AI based applications are playing a vital role to assist mental health. Our purpose is to study the role of AI in mental health.